Towards the biotechnological isomerization of branched sugars: D-tagatose-3-epimerase equilibrates both enantiomers of 4-C-methyl-ribulose with both enantiomers of 4-C-methyl-xylulose - Rao, D; Yoshihara, A; Gullapalli, P; Morinioto, K; Takata, G; da Cruz, F; Jenkinson, S; Wormald, M; Dwek, R; Fleet, G; Izumori, K (2008)
Microbial oxidation of 2-C-methyl-d-ribitol and 2-C-methyl-d-arabinitol by Gluconobacter thailandicus NBRC 3254 produces 4-C-methyl-l-ribulose and 4-C-methyl-d-ribulose, respectively. Further, 4-C-methyl-l-ribulose and 4-C-methyl-d-ribulose were equilibrated by d-tagatose-3-epimerase (DTE) with 4-C-methyl-l-xylulose and 4-C-methyl-d-xylulose, respectively. These transformations demonstrate that polyol dehydrogenase and DTE act on branched synthetic sugars. The green preparation of all of the stereoisomers of 4-C-methyl pentuloses illustrates the ability of biotechnology to generate novel branched monosaccharides. © 2008 Elsevier Ltd. All rights reserved.